Research Focus International Scientific Journal 2 (12) - Research Focus International Scientific Journal (Research Focus International Scientific Journal, 2024)
It is intended for scientists, teachers, researchers and specialists of various fields of higher education and research institutions. The editorial staff consists of a team of famous scientists who have achieved high scientific achievements in the fields of humanities, concrete and natural sciences of the countries. The topics of the articles are very diverse. They may reflect the results of scientific works related to PhD and DSc theses, as well as works containing other scientific research and scientific news.